2016
DOI: 10.1097/md.0000000000005372
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and feasibility of en bloc transurethral resection of bladder tumor versus conventional transurethral resection of bladder tumor

Abstract: Background:The aim of this meta-analysis was to compare the feasibility of en bloc transurethral resection of bladder tumor (ETURBT) versus conventional transurethral resection of bladder tumor (CTURBT).Methods:Relevant trials were identified in a literature search of MEDLINE, EMBASE, Cochrane Library, Web of Science, and Google Scholar using appropriate search terms. All comparative studies reporting participant demographics, tumor characteristics, study characteristics, and outcome data were included.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 24 publications
6
43
1
7
Order By: Relevance
“…Although whether ERBT, compared with conventional TURB, could provide a better long-term survival for patients with NMIBC is controversial, a recent metaanalysis in which patients who received ERBT showed a significantly lower 24-month recurrence rate than that of patients who received conventional TURB [10]. In our study, 2 patients who experienced disease recurrence were in the TURB group.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Although whether ERBT, compared with conventional TURB, could provide a better long-term survival for patients with NMIBC is controversial, a recent metaanalysis in which patients who received ERBT showed a significantly lower 24-month recurrence rate than that of patients who received conventional TURB [10]. In our study, 2 patients who experienced disease recurrence were in the TURB group.…”
Section: Discussionmentioning
confidence: 48%
“…Thus, whether RERBT remains a prophylactic effect for multifocal tumors or tumors of a larger size is unclear. However, to the best of our knowledge, we are the first to demonstrate that RERBT did not increase the number of cells in the bloodstream compared to conventional TURB, which may be a potential reason to explain the better oncological outcomes of patients who received ERBT than the outcomes of patients who were treated with conventional TURB [10,11]. We believe our preliminary study will encourage other groups conducting further prospective studies with larger sample sizes to gain insight into this field.…”
Section: Discussionmentioning
confidence: 79%
“…Finally, in a meta-analysis of 886 patients (438 en bloc, 448 cTURB) Wu et al proved that hospitalisation and catheterisation time were shorter in the en bloc group with no significant difference in operation time. Also, there was a significant difference in recurrence and complication rates in favour of en bloc resection [36].…”
Section: En Bloc With Electric Energymentioning
confidence: 93%
“…Although the clinical recurrence rate between two approaches is controversial, less intraoperative and postoperative complications have been observed when undergoing EBRT. A meta-analysis published in 2016 revealed that EBRT had a lower 24-month recurrence rate than CTURBT [25]. However, recent 4 RCTs revealed that no significant difference was found in terms of 24-month, 18-month or 12-month recurrence rate [7,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%